PERCEPTUAL RELATIONSHIP TO THE ACADEMIC SUPERVISION AND WORKING COMMITMENTS WITH PROFESSIONAL COMPETENCE OF TEACHERS - Samsul Arifin Hasibuan (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2020)
The data is analyzed by using simple correlation techniques, double correlation regression and partial correlation. The findings of the research are a significant link between perceptions of supervisory academic supervision with professional competence of teachers with ry1 of 0.567. the working commitment with professional competence of teachers with ry2 of 0.617 and perceptions of academic supervision of supervising work commitment together with professional competence of teachers with ry12 of 0.694. The study concluded that there was a significant link between perceptions of the academic supervision of supervisors and work commitments jointly with professional competence of teachers.